The impact of cross-border e-commerce on China : GDP, exports, and regional development - Zheng, Xiaoru; Burlakov, Georgi; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
Abstract Nowadays, cross-border e-commerce has a growing global influence. According to Pradeep R (2022) research, the global cross-border-B2C-e-commerce market was valued at $784.6 bill in 2021 and is projected to reach $7938.2 bill by 2031. (Pradeep R, 2022) Respectively, in an IPC survey, China s the most popular overseas online shopping market, with 30% of respondents saying they shop on e-commerce websites in China and 17% of cross-border transactions in AliExpress. (IPC, October 13, 2023).This thesis aims to study the impact of cross-border e-commerce in China on China's GDP and exports. In addition, it also investigates the impact of e-commerce in different regions of China on GDP. The author proposes hypotheses by studying the definitions and theories related to e-commerce, economic growth, and regional economy. Then, relevant data from China from 2002 to 2022 was collected, and an OLS model was established to draw relevant conclusions.
Vedoucí práce: Georgi Burlakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses